The Politeness Strategies Found in @kulinersby’s Instagram Account in Promoting Culinary Businesses - Joshua Delbert Gunawan; Nani Indrajani Tjitrakusuma (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2021)
This study aims to find out the types of politeness2 that are found in @kulinersby’s promotion culinary business promotion, and from there, the comments that are included as politeness1. The analysis is based on the theories of Brown and Levinson (1987) and Watts (2003). Watts (2003) states that what is theoretically considered as politeness (politeness2) in Brown and Levinson (1987) may not be the case in reality (politeness1). This qualitative study is limited to video-based posts, with the comments only related to how the account’s administrator promotes culinary businesses. From this research, the writers find that even though both politeness2 and politeness1 conflict with each other, there are some similarities that are found in analyzing both politeness. In conclusion, despite the lasting influence of Brown and Levinson’s (1987) theory, it still has some notable flaws, notably with universality and multiple interpretation of the strategies by different individuals, among others.